Opportunities of Natural Plant Materials as Alternative Antibacterials in Drinking Water Disinfection: Review Article - Ahmad, Rahwan; Prasetyawati, Prasetyawati; Assagaf, Farha; Kaluku, Khartini (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2025)
Various efforts to kill pathogenic bacteria in water with safer and more economical disinfectants continue to be pursued. The presence of antibacterial agents in plants can be a promising alternative to natural disinfection. This review discusses the use of natural materials as safer and more economical alternative disinfectants in the water disinfection process. Methods, This is a narrative review using sources from the ProQuest database. The key terms “Extracts AND Plants AND "Natural Compounds" AND "secondary metabolites" AND Antibacterial AND Pathogens AND water AND Escherichia coli” were used. Of the 45 studies found during the search phase, 12 were eligible for inclusion in this review. Results, This study shows that natural Plant Extracts have many uses not only as food ingredients but also as protection against various infectious diseases. Plant extracts as natural ingredients have active antibacterial compounds such as tannins, alkaloids, flavonoids, saponins and phenols which are sourced from seeds, flowers, leaves, bark and roots. Active compounds in plants can reduce or even eliminate pathogenic bacteria in water. Conclusion, Natural plant extracts have compounds that can kill pathogenic bacteria in water. Further studies on the use of natural plant extracts need to be carried out as alternative water disinfection materials that are easy to obtain, safe and economical.